PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP MOTIVASI DAN PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM KELAS VI SD GUGUS III SEKUPANG BATAM - Supri Retnowati; Ucu Rahayu; Sarmini Sarmini (Jurnal Dedikasi Pendidikan, 2023)
This study is intended to analyze the effect of the application of the model Problem-Based Learning on student learning motivation and improvement of learning outcomes of Natural Sciences grade VI SD Group III Sekupang, Batam. The variables studied are the application of problem based learning, student motivation, and improvement of learning outcomes. The research method used a quantitative approach using a quasi-experimental design with pretes-postes control group. Sampling of research with Purposive Sampling technique, namely 30 student from SDN 011 Sekupang as an experimental class, and 30 student from SDN 012 Sekupang as  a control class. Research instruments use learning outcomes tests, motivation questionnaires, and observation sheets. Data analysis techniques use descriptive statistic, and regression. From the results of Wilcoxon analysis, it is obtained that there is a difference in posttest learning results between the control class and the experimental class with a probability value (p) of 0.004 <0.05. So it can be concluded that the application of "Problem-Based Learning has an effect on student learning outcomes. There is no difference in student motivation in the application of problem based learning model with probability value (p) 0.194> 0.05